Efektivitas Penegakan Sanksi Hukum Terhadap Pelanggaran Baku Mutu Udara Di Wilayah Industri - Syabilal Ali; Adiatma Nugroho; Jimmi Dohar Pandapotan; Irwan Triadi (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Indonesia's land is not doing well now, because there is a lot of pollution, especially air pollution, which is very worrying. It was proven that in Jakarta in 2021, for 3 (three) days, the sky in Jakarta was covered with fog, which turned out to be pollution. It was created by the people of Jakarta, starting from factory fumes, then motor vehicle fumes. Based on the example above, there are actually regulations that regulate the monitoring and/or control of fumes coming out of factories or motorized vehicles, but up to now there are still many people being overlooked regarding air pollution. The method used in this research is normative juridical or library research, with a statutory approach to issues. That protection for the public against air pollution in general already exists in Law Number 32 of 2009 concerning Environmental Protection and Management Jo. Government Regulation Number 41 of 1999 concerning Control of Air Pollution, but the implementation regarding law enforcement by Environmental Law Enforcers is not optimal, so there is a need for cooperation between the community and the government.